Grant Hackett's Full Stroke at 475 m of His 800 m Gold Medal Race at the 1997 Pan Pacific Championships, Fukuoka, Japan - Rushall, B. S.
Video pictures (17 frames) and the appropriate technical/ biomechanical explanations for Grant Hackett's full stroke at 475 m of his 800 m gold medal race at the 1997 Pan Pacific Championships, Fukuoka, Japan. The outstanding good features of Grant Hackett's stroke are: the directness of propulsive forces that are horizontal and positioned under the body, particularly in the latter half of the pull, the outstanding "elbow-up" stroke of the right arm, generally good streamlining that only appears to be disrupted during inhalation in the breathing action, and overall length of the effective pull.